Digital Constitutionalism and the Future of Human Rights: A Comparative Review - Teravosa, Gillan; Nagari, Sulthon Bangun (Indonesian Scientific Publication, 2025)
This study presents a comprehensive narrative review of the evolving relationship between constitutionalism and the protection of human rights in various global contexts. The primary aim is to explore how constitutional frameworks adapt to contemporary challenges and uphold human rights amid increasing political complexity and technological transformation. A rigorous literature search was conducted using databases such as Scopus, Web of Science, and Google Scholar with keywords including